1991
DOI: 10.1128/mcb.11.2.963
|View full text |Cite
|
Sign up to set email alerts
|

Structural and antigenic polymorphism of the 35- to 48-kilodalton merozoite surface antigen (MSA-2) of the malaria parasite Plasmodium falciparum.

Abstract: Merozoite surface antigen MSA-2 of the human parasite Plasmodiumfalciparum is being considered for the development of a malaria vaccine. The antigen is polymorphic, and specific monoclonal antibodies differentiate five serological variants of MSA-2 among 25 parasite isolates. The variants are grouped into two major serogroups, A and B. Genes encoding two different variants from serogroup A have been sequenced, and their DNA together with deduced amino acid sequences were compared with sequences encoded by othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
108
1
2

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 28 publications
2
108
1
2
Order By: Relevance
“…But it has been shown that, despite the abundant intragenic recombination within Csp CR, there is an apparent absence of recombination between 5Ј and 3Ј NR, suggesting that the duplication and deletion of RATs occur by mitotic processes such as SSM 25 . SSM has also been implicated 28 as the cause of repeat variation in Msp2. However, it is interesting to note that among Ͼ100 field isolates from which Msp2 has been sequenced and entered in GenBank, only six have hybrid 3D7/Camp-FC27 sequences, despite the strong bias towards sequencing isolates with unusual serotyping results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…But it has been shown that, despite the abundant intragenic recombination within Csp CR, there is an apparent absence of recombination between 5Ј and 3Ј NR, suggesting that the duplication and deletion of RATs occur by mitotic processes such as SSM 25 . SSM has also been implicated 28 as the cause of repeat variation in Msp2. However, it is interesting to note that among Ͼ100 field isolates from which Msp2 has been sequenced and entered in GenBank, only six have hybrid 3D7/Camp-FC27 sequences, despite the strong bias towards sequencing isolates with unusual serotyping results.…”
Section: Discussionmentioning
confidence: 99%
“…For example, A1 alleles possess four amino acid motifs, whereas a repeating eight amino acid motif occurs in A3. Fenton et al have shown that the allelic subclasses within the 3D7/Camp family are derived from a common ancestral nucleotide sequence and that the diversity arises from duplication and deletion of repeat subunits 28 .…”
Section: Merozoite and Sporozoite Surface Antigensmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8,[20][21][22] Including all the parasite's genetic variants (thousands) involved in invasion, thereby trying to saturate the immunologic system for preventing a single parasite's escape from the immune response would be an impossible task, even more so when these genetic variants are found very close to functionally relevant amino acid sequences (such as those binding to host cells), thus biasing the immune system toward responding against functionally irrelevant regions.…”
Section: Rationale For Subunit-based Synthetic Peptide Vaccine Develomentioning
confidence: 99%